Penerapan Metode Just In Time sebagai Alternatif Pengendalian Persediaan Bahan Baku Pada PT BEHAESTEX, Pandaan Pasuruan - sri dwi ningsih; Andhika Ari Pratama (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
This study aims to determine the most effective and cost-effective use of the yarn raw material inventory method at PT Behaestex, Pandaan, by comparing the conventional methods used in the company at this time with the Just In Time (JIT) method. The data used are the total inventory of yarn raw materials and data on purchasing raw materials for yarn at the PT Behaestex, Pandaan Company in 2020. This study uses a quantitative descriptive method so as to describe the data with numbers. From the analysis using the Just in time system, it can be concluded that the Just In Time system is more efficient in calculating the total inventory cost of approximately 87% than the conventional method used by the company today.Keywords: Inventory, Raw Materials, Cost and just in time (JIT).